Samarium(III) Picrate Tetraethylene Glycol Complex: Photoluminescence Study and Active Material in Monolayer Electroluminescent - Kusrini, Eny; Saleh, Muhammad Idiris; Yulizar, Yoki; Za'aba, N.K.; Abd Majid, Wan Haliza (Elsevier, 2011)
A mononuclear Sm(III) complex involving Pic and EO4 (where Pic= picrate anion and EO4= tetraethylene glycol) has been studied. It shows a bright-orange emission when used as active material in a monolayer electroluminescent device of ITO/EO4-Sm-Pic/Al. The crystal structure of the complex consists of Sm(Pic)(2)(H2O)(EO4)(+) cation and Pic(-) anion. The Sm(III) ion is coordinated with nine oxygen atoms from one EO4 ligand in a pentadentate mode, two Pic anions each in bidentate and monodentate modes, and one water molecule. Both the terminal alcohol groups of the acyclic EO4 ligand were involved in the O-H center dot center dot center dot O hydrogen bonding by infinite one-dimensional (1D) chain within a symmetry direction 0 1 0. The photoluminescence (PL) spectrum of the thin film shows the typical spectral features of the Sm(III) ion (4G(5/2)-> 6H(7/2) transitions). The root-mean-square (rms) of the roughness of thin film is 30.605 nm and indicates that the formation of the monolayer electroluminescent device is not uniform and retains a high crystallinity. Typical semiconductor current-voltage (I-V) property was also observed in this device with threshold and turn voltages of 2.8 and 6.2 V, respectively. The Sm(Pic)(2)(H2O)(EO4)(Pic)center dot H2O complex can be applied as a luminescent center in OLED for bright-orange emission. (C) 2011 Elsevier B.V. All rights reserved.